2007
DOI: 10.1007/s12098-007-0208-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple organ dysfunction syndrome following single wasp sting

Abstract: Wasp stings have been associated with wide variety of reactions from mild local reaction like wheal formation to fatal systemic reactions. Life threatening complications following a single wasp sting are relatively rare and unexpected. We report here the clinical course of a 12 year old child who developed Multiple Organ Dysfunction Syndrome (MODS) and died after a single wasp sting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…They are all able to deliver a painful sting, however, the response to which can vary from no or localized reaction up to systemic reaction, organ dysfunction, or multiorgan failure, including death [1,15]. Wasp sting causing anaphylaxis is a well-known lifethreatening condition, and usually an immediate reaction to the sting.…”
Section: Introductionmentioning
confidence: 99%
“…They are all able to deliver a painful sting, however, the response to which can vary from no or localized reaction up to systemic reaction, organ dysfunction, or multiorgan failure, including death [1,15]. Wasp sting causing anaphylaxis is a well-known lifethreatening condition, and usually an immediate reaction to the sting.…”
Section: Introductionmentioning
confidence: 99%
“…Sharmila et al (1) reported MODS and death after a single wasp sting in a 12-year-old boy. Our patient also had MODS after a single wasp sting and could not be saved.…”
Section: Discussionmentioning
confidence: 99%
“…A wasp sting is a commonplace occurrence in tropical areas and sometimes may lead to serious complications including anaphylaxis, renal failure, multiple organ dysfunction syndrome (MODS) and various neurological manifestations (1)(2)(3)(4)(5)(6)(7). MODS usually occurs after multiple wasp stings and is rare after a single sting (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However a fatal case of child with multiorgan dysfunction syndrome after a single wasp sting has also been reported 8 . The morbidity therefore may depend not only upon number of stings but also on the strength of venom and susceptibility of children.…”
mentioning
confidence: 99%